2048. Comparison Between Endpoint and Real-Time (RT) Polymerase Chain Reaction (PCR) for the Diagnosis of Pneumocystis Pneumonia (PCP). (26th November 2018) - Zhou, Shiwei; Kauffman, Carol A; Bachman, Michael A; Miceli, Marisa H
Abstract: Background: The definitive diagnosis of PCP requires direct visualization of the organism by silver or direct fluorescent antibody stain, but in recent years PCR has become a widely used diagnostic tool. Varying results have been noted with different PCR assays; one concern has been that RT-PCR will be more sensitive and not differentiate colonization from infection. For this study, we compared the performance of RT-PCR with that of endpoint PCR for detection of PCP. Methods: All adult patients who had a bronchoalveolar lavage (BAL) or sputum sample positive for Pneumocystis by PCR at the U. Michigan Hospitals from February 2014–February 2018 were studied. Before February 2017 samples were tested with endpoint PCR followed by agarose gel electrophoresis and after February 2017 with RT-PCR. For each patient, a strict case definition based on host factors, clinical presentation, radiological and pathologic findings, was used to classify PCP as proven, probable, possible, and unlikely. Based on this classification, endpoint PCR and RT-PCR results were designated as true positive or false-positive presumably colonized (FP). Results: The number of specimens tested each year was similar, ranging from 751 to 791. One hundred and fifty-three patients tested positive: 77/2318 (3%) by endpoint PCR and 76/783 (10%) by RT-PCR. One hundred and twenty-six patients had risk factors for PCP: hi-dose steroids (39), hematologic malignancy (38), chemotherapy within 3 months (24), HIV (14), solid-organ transplant (12), stem cell transplant (9), and 27 patients had no PCP risk factors. By our definitions, patients were classified as proven (2), probable (70), possible (46) and unlikely (35). RT-PCR gave a higher FP rate (27/76, 35%) than endpoint PCR (8/77, 10%, ) P < 0.0001, especially in those with chronic lung disease, P = .001 and those with no known PCP risk factors, P < 0.0001. More patients with no risk factors tested positive with RT-PCR (20) than with endpoint PCR (7), P = .006. FP rates RT-PCR were similar in sputum (34%) and BAL (36%). Conclusion: RT-PCR gave significantly more FP results, likely due to increased detection of Pneumocystis colonization. Pretest probability should be considered when ordering a highly sensitive test such as RT-PCR and positive results must be interpreted in the context of the clinical presentation, radiological findings and risk factors. Disclosures: All authors: No reported disclosures.